PEMANFAATAN MEDIA BUSUU ONLINE UNTUK MENINGKATKAN KOMPETENSI GURU BAHASA INGGRIS SD TERHADAP KEMAMPUAN KOSAKATA (VOCABULARY) DAN BERBICARA (SPEAKING) - widi winarso; Ferawaty Puspitorini; Kardinah Indrianna; Mulyadi; Rorim Panday; Tutiek Yoganingsih (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
ABSTRACT The purpose of this research is to improve the competence of English language vocabulary of junior English teachers by utilizing the online busuu media. The method used in this research is descriptive method. The sample in this research is teachers of SD Yasporbi Jakarta. Researchers provide vocabulary and speaking test before treatment (pre-test) using online busuu media in the form of multiple choice, and vocabulary and speaking test after treatment (post-test) using online busuu media. The results of this study indicate an increase in listening skills as indicated by an increase in the value of post-test. Key Words: Media, Online, Busuu, Vocabulary, Speaking, English